PEMBERDAYAAN PETANI DALAM PENGELOLAAN IRIGASI BERBASIS ENERGI SURYA MELALUI PEMASANGAN SOLAR PUMP DI NAGARI TANJUNG BARULAK: Empowering Farmers through the Adoption of Solar-Powered Pump Technology in Nagari Tanjung Barulak, Tanah Datar Regency - Insannul Kamil; Is Prima Nanda; Ilhamdi Rusydi; Devi Chandra; Nurhamidah Nurhamidah; Ridwan Ridwan; Dendi Adi Saputra; Prima Fithri; Febi Putri Yastari (LPPM Universitas Andalas, 2026)
This community engagement program aims to improve irrigation efficiency and reduce farmers' dependence on rain-fed water through the implementation of solar-powered pumping technology in Nagari Tanjung Barulak, Tanah Datar Regency, West Sumatra, Indonesia. The program adopted a Participatory Action Research (PAR) approach, actively engaging farmers in the planning, installation, training, and evaluation of the irrigation system. The intervention included the installation of a 25 kWp solar-powered pumping system equipped with photovoltaic (PV) panels and a DC submersible pump, followed by operational and maintenance training for approximately 30 farmers. The results demonstrated that the system was capable of irrigating approximately 100 hectares of agricultural land on a rotational basis, increasing irrigation water availability by up to 60% compared with previous conditions. In addition, irrigation operating costs were reduced by approximately 40% due to decreased reliance on fossil fuels. Farmers' knowledge and technical skills also improved substantially, with 85% of participants able to operate the system independently after completing the training. The program produced a fully functional solar-powered pumping system, practical training modules, and a community-based irrigation management group to ensure long-term sustainability. Overall, the findings indicate that implementing solar-powered irrigation through a participatory approach is an effective strategy for enhancing irrigation efficiency, lowering production costs, and strengthening farmers' capacity to manage water resources independently. The program offers a scalable and sustainable model that can be replicated in other regions with similar environmental and socio-economic characteristics.